2008
DOI: 10.1111/j.1574-6941.2007.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

A strain of Lactobacillus plantarum affects segmented filamentous bacteria in the intestine of immunosuppressed mice

Abstract: Segmented filamentous bacteria (SFB) are present in the gastrointestinal tract of mice from weaning until the maturation of the immune system. Probiotic bacteria also have an effect on host immunity. To study the relationships established between these bacteria, samples from a mouse model fed with Lactobacillus plantarum under different immunological conditions were analysed. SFB populations were measured by a newly designed group-specific quantitative PCR assay. The results confirmed the presence of the probi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 28 publications
1
25
1
Order By: Relevance
“…28 The high increment in the number of SFB found in ileum samples of immunosuppressed mice was restored to normal values when animals received a strain of Lactobacillus plantarum. 29 Importantly, recent data obtained with two complimentary genetic mouse models, demonstrated that Paneth cell alfa-defensins play a crucial role in regulating microbial ecology. In particular these antimicrobial peptides induce striking losses of SFB and fewer IL-17-producing T cells in the small intestinal lamina propria; this observation provides evidence for a key role of alfa-defensins in regulating intestinal microbial ecology in general and SFB homeostasis in particular.…”
Section: Resultsmentioning
confidence: 99%
“…28 The high increment in the number of SFB found in ileum samples of immunosuppressed mice was restored to normal values when animals received a strain of Lactobacillus plantarum. 29 Importantly, recent data obtained with two complimentary genetic mouse models, demonstrated that Paneth cell alfa-defensins play a crucial role in regulating microbial ecology. In particular these antimicrobial peptides induce striking losses of SFB and fewer IL-17-producing T cells in the small intestinal lamina propria; this observation provides evidence for a key role of alfa-defensins in regulating intestinal microbial ecology in general and SFB homeostasis in particular.…”
Section: Resultsmentioning
confidence: 99%
“…bulgaricus and Streptococcus salivarius ssp. thermophilus (group A) and other 10 skimmed fermented goats' milks manufactured with these starters and Lactobacillus plantarum C4 (group B), a putative probiotic strain previously isolated and tested (Bujalance et al, 2007;Fuentes et al, 2008;Puertollano et al, 2008), were analyzed. The production process of these fermented goats' milks has been previously published (Bergillos-Meca et al, 2013b;Moreno-Montoro et al, 2013) and it is detailed in the next section.…”
Section: Milk and Fermented Milk Samplesmentioning
confidence: 99%
“…Lactobacillus plantarum C4 was isolated from kefir grains and characterized as a potential probiotic strain with ability to partially restore immunity in mice immunosuppresed with cyclophosphamide [15]. This restorative effect was associated with normalization in the number of segmented filamentous bacteria, a bacterial population that has been linked to the maturation of the intestinal immunity and which was expanded in cyclophosphamide-immunosuppresed mice [16]. Recently, it has been demonstrated that L. plantarum C4, when administered to mice by the oral route, promoted the diversity of lactobacilli in the gut [17].…”
Section: Introductionmentioning
confidence: 98%